2000
DOI: 10.1007/s001980070083
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Risedronate Treatment in Postmenopausal Women: Effects on Biochemical Markers of Bone Turnover

Abstract: The development of new biochemical markers has made it possible to assess the effects of therapeutic agents on bone turnover more rapidly and precisely. In this early phase II study, we analyzed the effects of short-term, high-dose treatment with risedronate, a potent pyridinyl bisphosphonate, on markers of bone resorption and formation. Resorption markers included urinary free deoxypyridinoline (D-Pyr) crosslinks, N-terminal telopeptide (NTx) and C-terminal telopeptide (CTx) type I collagen crosslinks. Bone f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 7 publications
2
14
0
4
Order By: Relevance
“…Treatment with once-monthly ibandronate significantly reduced median serum CTX-I within 3 days of treatment initiation. Though prior studies have found clinically relevant changes in markers of bone resorption within 7 days of bisphosphonate initiation [5,15], this study demonstrates that significant changes in serum CTX-I levels are evident as early as 3 days after ibandronate administration. We also observed reductions in bone ALP levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Treatment with once-monthly ibandronate significantly reduced median serum CTX-I within 3 days of treatment initiation. Though prior studies have found clinically relevant changes in markers of bone resorption within 7 days of bisphosphonate initiation [5,15], this study demonstrates that significant changes in serum CTX-I levels are evident as early as 3 days after ibandronate administration. We also observed reductions in bone ALP levels.…”
Section: Discussionmentioning
confidence: 80%
“…Many bisphosphonate clinical trials have examined changes in BTMs at intervals of 1-3 months or longer [7,12,14], but recent studies find significant changes in BTMs from baseline within the first few weeks of therapy [5,6,15]. Monthly ibandronate was recently found to reduce serum CTX-I by 70% 7 days after administration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bu biyokimyasal markırlar, kemik yapımının ve yıkımının izlenmesinde kullanılmaktadır 22 . Kemik yapım ve yıkımının biyokimyasal markırları dolaylı yoldan kemik kaybının hızı hakkında fikir vermekte ve böylece osteoporöz gibi metabolik kemik hastalıklarının risk tayininde, tedavi seçiminde ve tedavinin etkinliğinin değerlendirilmesinde fayda sağlamaktadırlar 23 . Yakın zamanda yapılan çalışmalarda bu markırların kemik turnover hızındaki anomalileri tespit etmekte kullanılan geleneksel tetkiklere göre çok daha fazla duyarlı oldukları bildirilmiştir.…”
Section: Discussionunclassified
“…To determine bone loss velocity, Osteocalcin and CTx are mostly used as bone cycle indicators. One of the markers of bone turnover speed in blood is Osteocalcin, and of the bone destruction is CTx (Raisz et al 2000;Koç et al 2004). The aim of this study is to comparatively examine the effects of Whole body vibration (WBV) trainings on some biochemical values (Beta-CTx, Osteocalcin).…”
Section: Relevant Literaturementioning
confidence: 99%